Analiza systemowa w amerykańskiej nauce o państwie — geneza, główne założenia - Langer, Tomasz (Wydział Prawa i Administracji UAM, 1976)
The author suggests that the research for new methods in the political science in the USA, Which broadly use the concept of systems analysis, realy came into prominence after the Second World War. The impetus for it involved both theoretical and practical considerations. Three of these seem to be of particular importance. First, it became necessary to attempt to explain in some objective manner the failure of "democracy", and the rise of authoritarian political institutions in Germany during the inter-war period. Second, the rise of socialist countries in Europe. Third, the creation of new states in Asia and Africa, as a result of failure of the colonial empires. The first important presentation of systems approach in political science in the USA was made by David Easton. He was primarily concerned with portraying the relationships between a system and the environment in which it was located. He directed attention to the boundary between politics and other aspects of social life, and, postulated the existence of close relationship between the system and environment. Applying systems analysis to (political science, some researchers have developed lists of political functional requisites. One such list war developed by Gabriel Almond, who divides it into four input, and three output functions. The Gabriel Almond's attitudes to the systems analysis is strongly functional oriented. Heapplied the basic Talcott Parsons thesis to the political science considerations. Other scholar, K. W. Deutsch, presents systems analysis in a cybernetic framework. Political systems, from his point of view, are the self-controling, and self-organyzing communication net. Deutsch, however, does not limit his concern to the communication of information; in addition he wants to apply communication theory to the political decision making process, to the role and relative weight of mass media, compared with past memories, stereotypes and other media, and to areas of attetjon, perception and orientation, values and evaluation, goal-seeking, and decision making. The author stresses the fact that, as a scientific method, systems analysis concept, is nolt well developed yet. However, it presents a good background for interdisciplinary research of political institution in action. On the other hand, it cannot be tracted as a universal tool for analyzing all political phenomena.
System Analysis in the American Political Science. Genesis and the Basic Assumption